Estrategias comunicacionales para la alfabetización digital al personal docente de la Unidad Educativa Angel Polibio Chaves, periodo mayo - septiembre 2023 - Morocho Chimbo, Yomayra Nashely (2024)
The general objective of this work was to propose edu-communicational strategies to improve the digital literacy of the teaching staff of the Angel Polibio Chaves Educational Unit during the period May-September 2023. The idea to be defended was that these strategies would significantly improve the digital competencies of teachers. The methodology used combined quantitative and qualitative approaches: structured surveys were conducted with 103 teachers and semi-structured interviews with the rector and other representatives of the institution. The results revealed significant variability in the digital competencies of teaching staff and an urgent need for continuous training in the use of digital tools. The conclusions indicated the importance of digital literacy for the effective integration of ICT in teaching and the need to overcome barriers such as lack of training and resistance to change. Recommendations included the implementation of continuous training programs, improving technological infrastructure and fostering a culture of innovation and adaptation. These strategies are intended to create a more dynamic educational environment adapted to the demands of the 21st century.